2012
DOI: 10.1136/bmjopen-2011-000607
|View full text |Cite
|
Sign up to set email alerts
|

Suicides by persons reported as missing prior to death: a retrospective cohort study

Abstract: ObjectiveA first study to compare suicides by missing persons with other suicide cases.DesignRetrospective cohort study for the period 1994–2007.Geographical locationQueensland, Australia.Population194 suicides by missing persons and 7545 other suicides were identified through the Queensland Suicide Register and the National Coroners Information System.Main outcome measureχ2 statistics and binary logistic regression were used to identify distinct characteristics of suicides by missing persons.ResultsCompared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 22 publications
5
27
3
3
Order By: Relevance
“…Moreover, Sveticic et al (2012) supported the findings by Gibb & Woolnough (2007) to suggest missing persons at risk of suicide sometimes leave a suicide note. This is also paralleled in other general suicide research, which identified a note to be left in 33 per cent of suicides (Carretta et al, 2015).…”
Section: Missing Persons Suicide and Vulnerability Indicatorssupporting
confidence: 84%
See 3 more Smart Citations
“…Moreover, Sveticic et al (2012) supported the findings by Gibb & Woolnough (2007) to suggest missing persons at risk of suicide sometimes leave a suicide note. This is also paralleled in other general suicide research, which identified a note to be left in 33 per cent of suicides (Carretta et al, 2015).…”
Section: Missing Persons Suicide and Vulnerability Indicatorssupporting
confidence: 84%
“…Conversely, a suicide note was only observed in 18 per cent of this study's sample, which is much lower than the 43 per cent ascertained by Sveticic et al (2012). It must be mentioned that the presence of a suicide note was only considered if it had been found at the point when the person was reported missing.…”
Section: Missing Persons Suicide and Vulnerability Indicatorsmentioning
confidence: 53%
See 2 more Smart Citations
“…Studies reported that information in the NCIS may be inaccurate due to coding errors [ 61 63 ]. Whilst it was noted that the NCIS conducts a data quality program to review and correct information, this cannot be applied to all records [ 64 ].…”
Section: Resultsmentioning
confidence: 99%